Innovations in science teacher education in the Asia Pacific (Emerald, 2014)
The chapters in this book will focus on pre-service and in-service science teacher education, because both are equally important. With case studies for China, Japan, Korea and Taiwan topics include: Professional Development of Chemistry Teachers in the New Curriculum, Using Classroom Observation to Assist Teacher Professional Development and Science Teacher Education and Science as Inquiry: Promises and Dilemmas.
Keywords: Education -- Evaluation.; Education -- Teaching Methods & Materials / Science & Technology.; Education -- Multicultural Education.; Teacher assessment.; Examinations & assessment.; Science -- Study and teaching -- Asia.; Science -- Study and teaching -- Pacific Area.; Science teachers -- Training of -- Asia.; Science teachers -- Training of -- Pacific Area.; elektronické knihy; electronic books